2020
DOI: 10.1088/1361-6528/aba1bb
|View full text |Cite
|
Sign up to set email alerts
|

Graphene nanofillers as a player to improve the dynamic compressive response and failure behavior of carbon/epoxy composite

Abstract: Vast research has been going on to improve the mechanical performance of carbon fiber reinforced polymers composite (CFRP) when subjected to quasi-static loading but investigation and modification of their dynamic behavior are still underdeveloped. This paper presents an experimental investigation on the effect of randomly dispersed graphene nanoplatelets (GNPs) on the mechanical properties of CFRP composites under dynamic loading. Four different mass fractions of GNPs, 0%, 0.5%, 1%, and 2%, were considered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…The bending strength of the GNP/epoxy nanocomposites decreased peak stress and strain at break, Figures 6 and 7. This degradation has already been noted in some research [35][36][37], which has explained the poor dispersion of graphene. The formation of aggregates can cause a stress concentration.…”
Section: Bending Properties Of Gnp/epoxy Nanocomposites: Effect Of Gnpssupporting
confidence: 58%
“…The bending strength of the GNP/epoxy nanocomposites decreased peak stress and strain at break, Figures 6 and 7. This degradation has already been noted in some research [35][36][37], which has explained the poor dispersion of graphene. The formation of aggregates can cause a stress concentration.…”
Section: Bending Properties Of Gnp/epoxy Nanocomposites: Effect Of Gnpssupporting
confidence: 58%
“…There are quite a few studies in which the investigation on the compressive behavior of the graphene incorporated CFRPs has been done. [13][14][15] Hu et al reported an increase of 8.1% in the residual compressive strength of multilayer graphene reinforced CFRPs after a low velocity impact test. 13 These CFRPs were made by hand layup of a graphene-epoxy mixture onto woven carbon fabrics before hydraulically pressing.…”
Section: Introductionmentioning
confidence: 99%
“…Another study investigated improvement in the dynamic compressive response of the GNP-added CFRPs through split-Hopkinson pressure bar (SHPB) test compared to control CFRPs. 14 These CFRPs were manufactured through GNPs/epoxy mixing in three-roller mixer followed by hot pressing. An optimized amount (1 wt.%) of GNPs resulted not only improvement in elastic properties but also showed reduction in delamination, intralaminar cracking and crack propagation as observed using a high-speed camera system during testing and SEM thereafter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to use a one-dimensional approximation of axial wave propagation with good extraction of findings from input and output bars, isotropic materials were evaluated in traditional SHPB tests in a cylindrical shape with an L/D ratio roughly between 0.5 and 2 using different materials [9,10]. Materials, including soft polymers and biological tissues, have been tested at high strain rates using SHPB and their output signal contains less high-frequency noise in the signal because of their self-damping behaviour [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%